PENGARUH KOMPETENSI PEDAGOGIK GURU DAN FASILITAS BELAJAR SEKOLAH TERHADAP PRESTASI BELAJAR SISWA SMK N 1 MOTOLING TIMUR - Tiwow, Gilly; Wuisang, Jerry; Ranti, Devyano; Sumangkut, Luis (Literacy: Jurnal Pendidikan Ekonomi, 2025)
This study aims to determine the effect of Pedagogical Competence and School Learning Facilities on Student Learning Achievement at SMK Negeri 1 Motoling Timur. This study uses three variables, namely (X1) Pedagogical Competence variable, Learning Facilities (X2) and Student Learning Achievement (Y). Where (X1) and (X2) Using a questionnaire given to 50 students who are members of the class XI student population of SMK Negeri 1 Motoling Timur. The questionnaire uses a Likert scale with 15 questions, each alternative answer choice has a different score. While (Y) is measured using the report card results. The results of the Regression Equation are: Y = 56.76 + 0.28X1 + 0.16X2, this shows that there is an influence between pedagogical competence and learning facilities on student learning achievement, meaning that every 1 unit increase in the pedagogical competence and learning facilities variables will increase student learning achievement by. Keywords: Pedagogical Competence, Learning Facilities, Student Learning Achievement.